ANAMOSTIC LEXICAL METHODOLOGY FOR PHILOSOPHY STUDENTS - Mamatkulova Bakhtijon Ravshanovna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  The  article  explores  the  methodological  foundations  of  applying anamostic lexical methodology in teaching English to philosophy students. Anamostic lexical methodology focuses on the study of naming, conceptualization, and lexical meaning within philosophical discourse. This approach integrates linguistic, cognitive, and cultural aspects of language, allowing learners to understand how philosophical concepts are expressed and interpreted through specific lexical structures. The study emphasizes  the  importance  of  linking  philosophical  terminology  with  linguistic awareness  to  enhance  critical  thinking,  interpretation,  and  academic  writing  skills among philosophy students.